Wireless Smart Infusion Pumps: A Proposed Continuous Quality Improvement Data Analysis Process - Polisena, Julie; Hilfi, Hal; Bédard, Mario; Sedrakyan, Art (CMBES Proceedings, 2016)
Purpose: Errors associated with the use of infusion pumps can cause serious harm or death in hospitalized patients and increased costs to the health care system. Our study reviewed the continuous quality improvement (CQI) data collected from a wireless smart infusion pump device implemented at one of the largest Canadian teaching hospitals in a one year period. Methods: We reviewed the CQI summary data usage between April 27, 2014 and April 25, 2015 to assess Dose Error Reduction Software (DERS) compliance with the infusion pump’s master drug library (MDL) and the frequency of drug alerts. Also, we proposed a CQI data analysis process to audit the DERS compliance and frequency of pump alerts. Results: The CQI data indicated that DERS compliance with the infusion pump ranged from 72.14% to 100% depending on pre-defined clinical care areas (CCAs). The birthing unit, oncology, and critical care areas had the largest proportions of pumps alerts compared with the other CCAs. A CQI data analysis process was designed to monitor the performance of the wireless infusion pump system. Conclusions: The study findings provided information on patterns of use and risk reduction opportunities to inform the hospital’s goal to enhance the delivery of quality care and patient safety. We presented a CQI data analysis process to monitor the performance of the wireless infusion pump system, and a plan to evaluate the effectiveness, acceptability and safe implementation of the process at the hospital.